The Relationship Between Glycated Albumin and Time in Tight Range in Type 2 Diabetes - Jiaying Ni; Wenshuo Han; Yaxin Wang; Jiamin Yu; Wei Lu; Yufei Wang; Xiaojing Ma; Jingyi Lu; Jian Zhou (Journal of Diabetes)
ABSTRACT Aims Among the new glucose metrics derived from continuous glucose monitoring, the concept of time in tight range (TITR) has gained increasing attention. We aimed to assess the association between TITR and traditional glycemic indicators, such as glycated albumin (GA). Methods A total of 310 patients with type 2 diabetes on a stable glucose‐lowering regimen over the previous 3 months were enrolled. TITR and time in range (TIR) were calculated using continuous glucose monitoring data collected over a minimum of 5 days. Spearman correlation analysis was performed to assess the relationships between traditional glycemic indicators, including GA and HbA1c, with TITR and TIR. Receiver operating characteristic curves were used to evaluate the predictive value of GA for TITR > 50% and TIR > 70%. Results The median levels of GA and HbA1c were 15.6% (14.0%, 17.3%) and 6.5% (6.1%, 7.1%), respectively. Median TITR and TIR were 70.0% (56.0%, 81.0%) and 91.0% (84.0%, 96.8%), respectively. Spearman correlation analysis showed a moderate negative relationship between GA and both TITR and TIR. The optimal GA cutoff for identifying either TITR > 50% or TIR > 70% was 17.4%. Moreover, combining GA with fasting plasma glucose or 2‐h postprandial glucose significantly enhanced the ability to identify TITR > 50%, achieving performance comparable to the combination of HbA1c and plasma glucose. Conclusions In patients with type 2 diabetes, a GA cutoff of 17.4% effectively identifies TITR > 50%.